2022
DOI: 10.3390/v14051102
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vector Competence of Ixodes Ticks for Kemerovo Virus

Abstract: Tick-borne viruses are responsible for various symptoms in humans and animals, ranging from simple fever to neurological disorders or haemorrhagic fevers. The Kemerovo virus (KEMV) is a tick-borne orbivirus, and it has been suspected to be responsible for human encephalitis cases in Russia and central Europe. It has been isolated from Ixodes persulcatus and Ixodes ricinus ticks. In a previous study, we assessed the vector competence of I. ricinus larvae from Slovakia for KEMV, using an artificial feeding syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…KEMV titre was determined by plaque assay [ 8 ]. Cell culture plates (24-well) were seeded with BSR cells (1 × 10 5 cells/well) the day before titration.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…KEMV titre was determined by plaque assay [ 8 ]. Cell culture plates (24-well) were seeded with BSR cells (1 × 10 5 cells/well) the day before titration.…”
Section: Methodsmentioning
confidence: 99%
“…ticks [ 3 , 4 ], field vectors of this virus have not been formally identified. We previously assessed the vector competence of artificially infected I. ricinus from France and Slovakia and I. persulcatus ticks from Russia for KEMV and showed that it infects French and Slovakian I. ricinus and Russian I. persulcatus [ 8 ]. The infection rates of engorged larvae were comparable for French and Slovakian I. ricinus larvae and nymphs and I. persulcatus larvae.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations